2004
DOI: 10.1021/cg049867p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Growth Mechanism of Tellurium Nanotubes

Abstract: A simple hydrothermal reduction method, employing sodium tellurate (Na 2 TeO 4 ‚2H 2 O) as tellurium source and formamide (HCONH 2 ) as a reductant, was used to prepare and investigate tellurium nanotubes. The diameters of the nanotubes range from 200 to 600 nm and their lengths from 4 to 15 µm. Unlike studies reported previously, 1,2 a series of electron microscopy characterization results suggests that the growth of tellurium nanotubes under the present experimental conditions is governed by a nucleation-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 26 publications
9
96
0
Order By: Relevance
“…Reviewing the literature, it was found that the toxicity of the tellurite occurs via the two probable mechanisms: i) replacing the sulfur group in a number of amino acids and as a result creating non-functional proteins and ii) severely oxidizing the glutathione reservoir of the cells, which lead to the generation of excessive amounts of reactive Shakibaie M et al oxygen species (ROS) disrupting cell macromolecules involved in metabolic pathways (5,6). Recently, tellurium has been applied in the development of novel materials such as fl uorescent CdTe quantum dots (7,8) and diff erent telluride nanostructures (9), tellurium containing nanoparticles (NPs) (10), and tellurium nanotubes (11), which may fi nd potential applications in the electronics and medicine as a new fi eld of nanotechnology approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature, it was found that the toxicity of the tellurite occurs via the two probable mechanisms: i) replacing the sulfur group in a number of amino acids and as a result creating non-functional proteins and ii) severely oxidizing the glutathione reservoir of the cells, which lead to the generation of excessive amounts of reactive Shakibaie M et al oxygen species (ROS) disrupting cell macromolecules involved in metabolic pathways (5,6). Recently, tellurium has been applied in the development of novel materials such as fl uorescent CdTe quantum dots (7,8) and diff erent telluride nanostructures (9), tellurium containing nanoparticles (NPs) (10), and tellurium nanotubes (11), which may fi nd potential applications in the electronics and medicine as a new fi eld of nanotechnology approaches.…”
Section: Introductionmentioning
confidence: 99%
“…26 Other methods for wet chemical synthesis of 1D tellurium nanostructures are also reported. [27][28][29] However, the vapor phase synthesis of Te nanotubes is not common. In a particular case, it results in the formation of tubular structures of Te with micrometer diameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the crystal structure of Te is highly anisotropic with covalently bonded atoms forming unique helical chains which are bonded through weak Van Der Waals interactions [20]. This gives it a momentum towards 1D growth.…”
Section: Resultsmentioning
confidence: 99%